Turning carbon waste into an efficient and sustainable supercapacitor - Goren, Aysegul Yagmur; Dincer, Ibrahim (ELSEVIER SCI LTD, 2026)
Supercapacitors are considered promising energy storage devices due to their high power density, rapid charge-discharge capability, and excellent cycle stability; however, conventional activated carbon (AC) electrodes are often limited by low specific capacitance. In this study, a novel boron (B)-doped AC composite is synthesized via a green, low-temperature hydrothermal method using starch and vinegar as non-toxic, bio-based polymerization and doping agents. Structural and morphological characterizations confirmed effective B incorporation and the development of a porous carbon network. Electrodes fabricated from the raw AC and the B-doped AC composite are tested in symmetric supercapacitor configurations. The B-doped electrode presented a capacitance of 328.2 F/g at 0.1 A/g compared to the raw AC electrode (65.6 F/g), attributed to increased surface activity and enhanced pseudocapacitive behavior. Moreover, compared to the raw AC electrode, the B-doped AC electrode provided nearly twofold the power output across all cycles, starting at 0.22 W and maintaining significantly higher values throughout the discharge period, clearly demonstrating the enhancement effect of boron doping on power performance. Practical discharge performance is evaluated by charging the devices under various voltages and using them to power LEDs with different voltage ranges. The boron-doped supercapacitor showed longer discharge durations and better energy delivery, confirming its applicability for low-power electronics. Consequently, this work demonstrates a sustainable approach for developing high-performance supercapacitor electrodes using low-cost, renewable resources and highlights the beneficial role of boron doping in improving electrochemical energy storage.
Keywords: Energy; Energy storage; Supercapacitor; Waste; Sustainability; Environmental Impact; ORDERED MESOPOROUS CARBON; POROUS CARBON; PERFORMANCE; NITROGEN; ELECTRODE; Engineering